2022
DOI: 10.1002/ctm2.736
|View full text |Cite
|
Sign up to set email alerts
|

BSCL2/Seipin deficiency in hearts causes cardiac energy deficit and dysfunction via inducing excessive lipid catabolism

Abstract: Background Heart failure (HF) is one of the leading causes of death worldwide and is associated with cardiac metabolic perturbations. Human Type 2 Berardinelli‐Seip Congenital Lipodystrophy (BSCL2) disease is caused by mutations in the BSCL2 gene. Global lipodystrophic Bscl2 −/− mice exhibit hypertrophic cardiomyopathy with reduced cardiac steatosis. Whether BSCL2 plays a direct role in regulating cardiac substrate metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
(151 reference statements)
0
4
0
Order By: Relevance
“…Here, we found that Atp6v0d1 AKO mice display a similar developmental trajectory of cardiomyopathy to that observed in Bscl2 -/- mice, the most widely used animal model for studying lipodystrophy-related cardiomyopathy recapitulating human type 2 Berardinelli-Seip congenital lipodystrophy (BSCL2) disease, which progresses from compensated cardiac hypertrophy to heart failure 40 . Yet, loss of BSCL2 specifically in the myocardium also leads to the onset of cardiomyopathy 41 , adding the complexity of this model as whether dysfunctional AT or altered cardiac functions as the direct cause for cardiomyopathy. Moreover, the cardiomyopathy in Atp6v0d1 AKO mice can be rescued by increasing systemic insulin sensitivity with Rosiglitazone ( Figure S6 ), similar to that observed in Bscl2 -/- mice 42 , demonstrating the prominent feature of lipodystrophy cardiomyopathy that had been observed in the well-established Bscl2 -/- lipodystrophy mice.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that Atp6v0d1 AKO mice display a similar developmental trajectory of cardiomyopathy to that observed in Bscl2 -/- mice, the most widely used animal model for studying lipodystrophy-related cardiomyopathy recapitulating human type 2 Berardinelli-Seip congenital lipodystrophy (BSCL2) disease, which progresses from compensated cardiac hypertrophy to heart failure 40 . Yet, loss of BSCL2 specifically in the myocardium also leads to the onset of cardiomyopathy 41 , adding the complexity of this model as whether dysfunctional AT or altered cardiac functions as the direct cause for cardiomyopathy. Moreover, the cardiomyopathy in Atp6v0d1 AKO mice can be rescued by increasing systemic insulin sensitivity with Rosiglitazone ( Figure S6 ), similar to that observed in Bscl2 -/- mice 42 , demonstrating the prominent feature of lipodystrophy cardiomyopathy that had been observed in the well-established Bscl2 -/- lipodystrophy mice.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of lipid droplets with phagosomes containing pathogens occurs in response to infections, influencing the outcome or survival of the pathogen within host cells (Melo and Dvorak 2012 ). Thus, seipin could interfere in the capacity of macrophages to respond to pathogens through the lipid droplet metabolism and one-third of patients with congenital generalised lipodystrophy, a recessive condition caused by BSCL2 variants, died of infectious disease (Zhou et al 2022 ). Although patient EXOC18 had no noticed lipodystrophy previous to MIS-C, BSCL2 variants are also described in dominant clinical conditions (OMIM), which could explain the higher susceptibility to MIS-C.…”
Section: Discussionmentioning
confidence: 99%
“…Although patient EXOC18 had no noticed lipodystrophy previous to MIS-C, BSCL2 variants are also described in dominant clinical conditions (OMIM), which could explain the higher susceptibility to MIS-C. Furthermore, global lipodystrophic Bscl2 −/−mice exhibit hypertrophic cardiomyopathy with reduced cardiac steatosis, and mice with cardiac-specific deletion of Bscl2 developed systolic dysfunction with dilation, through excessive lipid catabolism (Zhou et al 2022 ). Curiously, patient EXOC18 presented Reentrant Supraventricular Tachycardias (RST) phenotype during the follow- up.…”
Section: Discussionmentioning
confidence: 99%
“…2 Not only is glucose aerobically oxidized more efficiently than FFAs, in metabolites compared with fatty acid–induced myocardial diastolic dysfunction, glucose maintains cellular homeostasis and reduces myocardial injury after ischemia. 3 Myocardium is rich in mitochondria, which determine cell death and survival through multiple pathways.…”
Section: Coronary Heart Diseasementioning
confidence: 99%